The effect of adding wheat and corn gluten to the diet of rats on the autoimmune and histopathological parameters in the intestine and liver - Recep Gümüş; Kübra Asena Terim Kapakin; Esra Manavoğlu Kirman; İsmail Bolat; Aybuke İmik; Nazlı Ercan (Revista Científica, 2024)
This study investigated the histopathological and immunohistochemical effect on the intestine and liver tissues with addition of the soybean meal (SBM), wheat Gluten meal (WGM) and Corn gluten meal (CGM) to rat diet. A total of 24 average twenty–day–old male rats (Wistar albino) were used in the study. The rats were randomly divided into 3 groups with 8 animals in each group (Control, Wheat and Corn groups). The diet provided to all three groups contained proteins, which were SBM, WGM and CGM in the Control, Wheat and Corn groups, respectively. In the study, the group fed with SBM was used as the Control group. Rats were fed a diet containing 22% crude protein and 2,598 kcal·kg-1 metabolic energy throughout the experimental period. The feeding trial was continued for a period of 50 days. Degenerative changes of varying severity in intestinal epithelial cells and atrophy in villi were observed. Similarly, the degenerative changes, especially vacuolar or hydropic degeneration were determined in hepatocytes. It was determined that the CD4 level were statistically significantly increased in the Wheat and Corn groups compared to the Control group (P<0.01) on intestine tissue. Also, it was determined that the IgA level was statistically significantly increased of the Wheat and Corn groups in liver tissue. (P<0.05). As a result, it was observed that the histopathological and immunohistochemical parameters of the intestine and liver tissues of the rats fed with diets containing highly WGM and CGM were limitedly affected.